Volume 1A: 35th Computers and Information in Engineering Conference 2015
DOI: 10.1115/detc2015-47856
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Parameters in Laser Engineered Net Shaping (LENS) Deposition of Multi-Materials

Abstract: During the past few years, metal based additive manufacturing technologies have evolved and may enable the direct fabrication of heterogeneous objects with full spatial material variations. A heterogeneous object has potentially many advantages and in many cases can realize appearance and/or functionality that homogeneous objects cannot achieve. In this work we employ a preprocess computing combined with a multi-objective optimization algorithm based on the modeling of the LENS deposition of multiple materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Optimized the process parameters with the help of mode FRONTIER ® software that helped minimize energy consumption and material wastes, and maximizes powder melting [38] Ti-Si-N coatings on Ti Higher hardness and wear resistant coatings on Ti (with varying ratios of Ti-Si, higher Ti content lead to higher hardness) [39] Lead zirconate titanate (PZT)…”
Section: Materials System Reported Functionality or Application Or Promentioning
confidence: 99%
“…Optimized the process parameters with the help of mode FRONTIER ® software that helped minimize energy consumption and material wastes, and maximizes powder melting [38] Ti-Si-N coatings on Ti Higher hardness and wear resistant coatings on Ti (with varying ratios of Ti-Si, higher Ti content lead to higher hardness) [39] Lead zirconate titanate (PZT)…”
Section: Materials System Reported Functionality or Application Or Promentioning
confidence: 99%
“…Lately, metal-based AM methods have evolved to produce direct fabrication of heterogeneous components with full spatial material distributions [85][86][87]. DED is one of the MMAM methods that falls into different processing categories, such as laser metal deposition (LMD), laser engineered net shaping (LENS) and direct metal deposition (DMD) [86].…”
Section: Direct Energy Deposition (Ded)mentioning
confidence: 99%
“…This study revealed an innovative way of enhancing mechanical and antibacterial properties of plasma-sprayed HA coating interfaces for load-bearing orthopedic as well as dental implant applications. In another study, Yan et al [85] optimized the process parameters on multi-materials, i.e., the fabrication of cermet composite using Inconel 718 and ceramic powders. The results show that in-housebuilt software helped to reduce energy usage and material waste while increasing powder melting.…”
Section: Direct Energy Deposition (Ded)mentioning
confidence: 99%
“…Repairs using DED have also been used in the field of aerospace to study the effectiveness of the process when being integrated as a tool to remanufacture IBR blades 6 . The process used in this work is laser blown powder directed energy deposition (LBP‐DED), which is similar to brazing, electron beam welding, wire and arc AM, and laser engineered net shaping (LENS™) 7‐10 . 11 This process feeds metal alloy powder into a laser path that is then melted onto the component in layers 12 .…”
Section: Introductionmentioning
confidence: 99%